2016
DOI: 10.1097/jom.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relation Between Work Hours and Cardiovascular Disease Risk

Abstract: Objectives To examine the presence of a dose-response relationship between work hours and incident cardiovascular disease (CVD) in a representative sample of U.S. workers. Methods Retrospective cohort study of 1,926 individuals from the Panel Study of Income Dynamics (1986–2011) employed for at least 10 years. Restricted cubic spline regression was used to estimate the dose-response relationship of work hours with CVD. Results A dose-response relationship was observed in which an average workweek of 46 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…Studies involving clinical disease have identified associations of long work hours with acute myocardial infarction, hypertension, CHD, stroke, biological functioning related to the development of CVD, disease pathways, and hematologic markers indicating an increased risk of CVD . Specific work hour thresholds have been associated with increased risk of CVD . In a low‐risk, employed population (Whitehall II Study), the addition of data on work hours to the Framingham risk score improved risk prediction of CHD by 4.7% .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies involving clinical disease have identified associations of long work hours with acute myocardial infarction, hypertension, CHD, stroke, biological functioning related to the development of CVD, disease pathways, and hematologic markers indicating an increased risk of CVD . Specific work hour thresholds have been associated with increased risk of CVD . In a low‐risk, employed population (Whitehall II Study), the addition of data on work hours to the Framingham risk score improved risk prediction of CHD by 4.7% .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][26][27][28]34 Specific work hour thresholds have been associated with increased risk of CVD. 28,29 In a low-risk, employed population (Whitehall II Study), the addition of data on work hours to the Framingham risk score improved risk prediction of CHD by 4.7%. 30 In the Atherosclerosis Risk in Communities study, work organization was associated with carotid intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long working hours have also been found to have significant adverse effects on many risk factors of CVD, such as depressive symptoms and sleep deprivation . Previous meta‐analysis studies conducted by European, US, and Australian researchers have demonstrated dose‐response relationships between working hours and the risk of CVD . In Taiwan, Cheng et al found that Taiwanese men who worked over 60 hours per week had a higher risk of CVD compared with those who worked 40‐48 hours per week.…”
Section: Introductionmentioning
confidence: 99%